Public policies to promote productive occupation and increase formality among the moderately poor: the Mexican agenda - Eduardo Sojo; Roberto Villarreal (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
Public policy aimed at building capacity among the extremely poor (support for food and nutrition; health; education and, more recently, financial services), combined with a stable macroeconomic environment, has proved to be successful for poverty alleviation in Mexico. Even though overall poverty is still very pronounced, about four million people originally in extreme or intermediate poverty registered real income gains during 2000-02 and entered moderate poverty, concentrated mostly in urban areas, where it exceeds extreme and intermediate poverty. Thus, the emerging challenge consists of defining and coordinating specific policies for the moderately poor, whose social and demographic characteristics and economic needs differ from those at deeper levels of poverty. At present, income generation among the moderately poor depends on informal employment, because structural factors impede these workers from participating in the formal sector. To foster social and economic development of this group, employment policies in general and policies to facilitate formal activities in particular, stand out as the key elements. Promoting greater formality among the moderately poor requires updating laws and regulations, but equally important, education, training, financial services, technical and administrative assistance for entrepreneurs, etc., must be applied for a sustainable increase in income. The policies should increase formality, which is important for improving income and social protection for the moderately poor; for integrating activities that can benefit from trading with each other, for increasing the competitiveness of the Mexican economy as a whole; for improving political governance and consolidating the rule of law. An integral support programme to raise productivity and income of the moderately poor and to promote their participation in the formal sector activities is outlined in this study. – inequality ; poverty ; income ; education ; gender ; employment
Keywords: E61; D13; G18; O17; 330; Armut; Armutspolitik; Mexiko